Psychographic determinants of private-label adoption: a feasibility study in the Portuguese yogurt market - Ana Oliveira Brochado; Susana Henriques Marques; Pedro Mendes (Tourism & Management Studies)
This study seeks to point out the main psychographic determinants of private-label brand proneness in a specific industry: the Portuguese yogurt market. This is a booming industry for store brands in Portugal, which account for nearly half of the total market share. An in-depth interview was held with a sales and marketing expert of the leading yogurt company in Portugal. Next, we conducted a survey targeting consumers of yogurt. Based on the results of a Tobit regression, we conclude that consumers base their decisions about private label versus national brands on three different types of variables: price-related variables, quality-related variables and variables related to involvement with the product category. Managerial implications are also discussed.